Readers' Perceptions. - Woods, Claire A.; Lushington, Kurt; Crichton, Jonathan (International Journal of the Book, 2007)
With an interest in the use of electronic book (eBook) reading devices (eBookRD ) as a means of providing texts for students, the authors have conducted research projects to evaluate student reaction to such devices. The effectiveness of the dedicated electronic book as a tool for either educational or recreational purposes is still debatable. It is also clear that the development of the eBookRD as a device is on-going and that devices currently on the market have not yet exploited electronic or digital technologies to their potential. At the same time, the use of digital media to represent the world or to interact with others and act on the world proceeds (as the conference notes suggest) at a ‘dizzying’ pace. Young people are champions at exploiting available technologies, re-creating language and modes of communication with text messaging and blogging. Their skills at creating texts or at 'reading' the visual cues in the media with which they surround themselves are obvious. We now consider the aesthetics of the reading experience, gauging student response and reaction to the book as practical tool / electronic object or as creative/ aesthetic artefact. Drawing on our backgrounds in psychology and communication and writing, we explore the book as aesthetic object and as tool. We explore student response to interacting with electronic books, digital texts and with the paper-based text - the book as we know it. We are interested not only in the practicalities of providing students with eBookRDs as a means of providing texts as educational tools, but also with the aesthetic pleasures of creating and responding to texts - the printed text, the multimodal and digital text/ the electronic text. Visual and textual culture have taken on dramatically new dimensions so that the book as performative (if on-line or in eform) because it demands a particular kind of interaction, or as spectacle (if it is a digital/ multimedia experience), or as art object (the printed book published with the resources of available technologies in ways vastly different from the mechanical modes of the past), evokes reactions and responses which are worthy of discussion and exploration.